Inequality and human development: The role of different parts of the income distribution - David Castells-Quintana; Carlos Gradín; Vicente Royuela (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
In this paper we reassess the relationship between inequality and human development, focusing on the differential effect associated with the concentration of national income at different parts of the income distribution. To do so, we rely on a large global panel of countries over the last decades which includes information on economic and human development as well as detailed information on the distribution of income within countries. We take advantage of detailed distributive data consistent across countries and over time (World Income Inequality Database companion datasets). We show how the concentration of income at the bottom and top, rather than overall inequality, is negatively associated with human development. This result highlights the relevance of income shares that go to the middle part of the income distribution and seems especially important in what refers to human capital accumulation in middle- and low-income countries and health in high-income countries. Our main results remain significant under different specifications and estimation techniques and after controlling for several country-specific characteristics, including the quality of institutions.
Keywords: O10; O15; O40; 330; human development; inequality; concentration; institutions